A Differential Hybridization Scheme to Identify Photoreceptor-Specific Genes - Swanson, Deborah A.; Freund, Carol L.; Steel, Jason M.; Xu, Shunbin; Ploder, Lynda; McInnes, Roderick R.; Valle, David

(untitled) (Genome Research, 1997)
Identification of genes expressed preferentially or exclusively in photoreceptors will facilitate the understanding of photoreceptor biology as well as provide candidate genes for inherited retinal degenerations. To achieve this goal we performed a differential hybridization screen of 3717 well-isolated phage clones from a human retinal cDNA library. Clones were selected for further study if they hybridized exclusively or strongly preferentially to a probe derived from RNA isolated from the cone-predominant retina of 13-line ground squirrels as compared to a probe derived from human fibroblast RNA. Twenty percent of clones (9/45) identified by this screen were derived from photoreceptor-specific genes and an additional 24.4% (11/45) were from neural-specific genes, demonstrating the utility of this strategy in identifying genes important for retinal biology.[The sequence tags of cDNAs identified in this screen have been deposited in GenBank under accession nos. U89715, U89878–U89888, andU89951–U89955.]